PERILAKU KONSUMSI MAKANAN CEPAT SAJI PADA REMAJA DAN DAMPAKNYA BAGI KESEHATAN - Icha Pamelia (Jurnal Ilmu Kesehatan Masyarakat, 2018)
Adolescent nutritional needs need to be considered because in adolescence there is rapid growth and development. Unhealthy eating habits will affect adolescent nutrition. Unhealthy foods such as fast food are consumed by teenagers. At a time when everything is modern like now, teenagers want everything to be fast, including in choosing food. Fast food is also known to the public as junk food. Junk food is defined as food waste or food that does not have nutrients for the body. Eating junk food is not only in vain, but can also damage health. Fast food comes from western countries which generally have high fat and calorie content. Many factors influence teenagers eating fast food. These factors are discussed based on research articles and book references. Factors that influence consumption of fast food include taste, price, a comfortable place, and peer influence. Fast food can increase the risk of several diseases, such as obesity, diabetes, hypertension, and disorders of blood fat or dyslipidemia. Obesity or obesity is experienced by many children, adolescents, and adults. Obesity occurs because of a changing lifestyle, including eating patterns that often consume fast food. Eating fast food too often does not only cause obesity. However, from obesity experienced by someone, it will increase a person's risk factors for other degenerative diseases, such as high blood pressure, diabetes, cancer, heart disease, and stroke.